Oral Leishmaniasis: diagnostic and therapeutic journey - Ferreira, Sonia Maria Soares; Oliveira, Catarina Rodrigues Rosa de; França, Glória Maria de; Abreu, Eulina Maria Vieira de; Silva, Ivisson Alexandre Pereira da; Santos, Anne Caroline Barbosa dos; Araújo, João Carlos de Melo; Lonni, Nicole; Silva, Caroline Alfaia; Rivero, Elena Riet Correa; Gondak, Rogério de Oliveira; Albuquerque-Júnior, Ricardo Luiz Cavalcanti de (Journal of Oral Diagnosis, 2025)
Leishmaniasis, caused by protozoan parasites, is a widespread infectious disease and a prominent example of neglected tropical diseases. Brazil is among the countries most severely affected by this condition globally. Mucocutaneous leishmaniasis rarely involves oral sites, presenting diagnostic challenges. This study explores a case of mucocutaneous leishmaniasis discussing clinical presentation, diagnostic process and treatment. An 85-year-old woman presented with a progressively enlarging, painful palatal ulcer. The patient had a history of treated tuberculosis and reported additional symptoms including breathing difficulties, nosebleeds, osteoarthritis, hearing loss, and insomnia. Initial biopsy showed ulcerated squamous epithelium and nodular granulomatous inflammation. Despite negative diagnostic tests for tuberculosis, syphilis, HIV, and viral hepatitis, sarcoidosis was initially considered but treatment was ineffective. Worsening symptoms later revealed structures consistent with Leishmania sp. amastigote forms, confirmed by immunohistochemistry, leading to a diagnosis of oral leishmaniasis. Treatment with liposomal amphotericin B resulted in successful management. The rarity of oral manifestations further complicates diagnosis, highlighting the critical role of dentists in conducting a thorough assessment, administering the correct treatment, and ensuring proper follow-up to guarantee patient compliance.